The Legal Strength of International Health Instruments - What It Brings to Global Health Governance? - Haik Nikogosian; Ilona Kickbusch (Kerman University of Medical Sciences, 2016)
Public health instruments have been under constant development and renewal for decades. International legal instruments, with their binding character and strength, have a special place in this development. The start of the 21st century saw, in particular, the birth of the first World Health Organization (WHO)-era health treaties - the WHO Framework Convention on Tobacco Control (WHO FCTC) and its first Protocol. The authors analyze the potential impact of these instruments on global health governance and public health, beyond the traditional view of their impact on tobacco control. Overall, the very fact that globally binding treaties in modern-era health were feasible has accelerated the debate and expectations for an expanded role of international legal regimes in public health. The impact of treaties has also been notable in global health architecture as the novel instruments required novel institutions to govern their implementation. The legal power of the WHO FCTC has enabled rapid adoption of further instruments to promote its implementation, thus, enhancing the international instrumentarium for health, and it has also prompted stronger role for national legislation on health. Notably, the Convention has elevated several traditionally challenging public health features to the level of international legal obligations. It has also revealed how the legal power of the international health instrument can be utilized in safeguarding the interests of health in the face of competing agendas and legal disputes at both the domestic and international levels. Lastly, the legal power of health instruments is associated with their potential impact not only on health but also beyond; the recently adopted Protocol to Eliminate Illicit Trade in Tobacco Products may best exemplify this matter. The first treaty experiences of the 21st century may provide important lessons for the role of legal instruments in addressing the unfolding challenges in global health.